Motivasi Kerja Pegawai Kantor Kelurahan Bontoramba Di Kabupaten Gowa - Firma, Ade; Hakim, Lukman; Sudarmi, Sudarmi (Universitas Muhammadiyah Makassar, 2022)
AbstractThis study aims to determine the role of motivation and inhibiting factors in improving the performance of employees at the Bontoramba Village Office. The type of research used is qualitative research methods and the type of research used is descriptive, collecting techniques using observation and interviews. The results of this study indicate that 1) Physical needs in the form of providing office facilities have been met. 2) Security needs, as well as civil servant discipline law at work. 3) social needs from the strength of kinship or friendship and coordination between other agencies in carrying out activities. 4) The need for appreciation, namely the provision of acknowledgment of self-esteem from the Regent. 5) Self-actualization of training or training development according to employee needs. The barrier to motivation is that there are still employees who can't operate computers and lack discipline in work, such as some who don't come on time.Keywords: Motivation, work, employees